The Influence of Perceived Ease And Usefulness on Students' Behavior Intention in Using Android Accounting Applications - Fauzan, Slamet; Moliani, Ayuneng Indah; Andryani, Andryani; Wahidah, Alfi Khoirul; Afqohani, Afqohani; Hidayat, Choirul; Wahyuningsih, Amanda Putri (Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2023)
The current era of disruption affects various fields, including the accounting field. Where this era gave rise to various accounting applications that can assist in the preparation of financial statements. Accounting applications that can be used today are not only computer-based but also Android-based. In connection with that, we want to examine how the effect of student perceptions on intentions to use an android-based accounting application. To be able to know the results, we used quantitative methods for the purpose of testing the hypothesis. Data were collected through questionnaires, but before the questionnaires were distributed we tested the validity and reliability of the research instrument. After being declared valid and reliable, questionnaires were distributed to research subjects, namely Accounting Students, Faculty of Economics, State University of Malang. Next, we analyzed the data starting with the classical assumption test and continued with simple and multiple regression tests. From the results of data testing, it can be seen that students' perceptions of the usefulness of android-based accounting applications have a positive effect on intention to use. In addition, student perceptions of the ease of use of android-based accounting applications also have a positive effect on intention to use. Finally, the two perceptions, namely the perception of usefulness and ease of use simultaneously affect the intention to use an android-based accounting application. In connection with that, it is hoped that the results of this study can contribute to the development of an Android-based accounting application which can also improve the performance of accountants.